2001
DOI: 10.1046/j.1460-2695.2001.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behaviour of PC/ABS resin under mixed‐mode loading

Abstract: Fracture behaviour of polycarbonate (PC)/acrylonitrile‐butadiene‐styrene (ABS) under mixed‐mode loading conditions was studied for several weight fractions of PC and ABS. Mode I and mixed‐mode fracture tests were carried out by using compact–tension–shear specimens. At a certain value of mixed‐mode loading ratio KII /KI  a crack of the shear type will initiates at the initial crack tip. Fracture toughness increases under mixed‐mode loading with an increase in the mode II component, whereas it reduces with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…9. The first pair of cracks are 'shear-like cracks' that were also observed by Husaini et al [2]. Formation of the first pair of cracks can be explained by the competition of maximum principal stress and maximum shear stress [17].…”
Section: Iosipescu Test On Specimens Without Groovesmentioning
confidence: 84%
See 3 more Smart Citations
“…9. The first pair of cracks are 'shear-like cracks' that were also observed by Husaini et al [2]. Formation of the first pair of cracks can be explained by the competition of maximum principal stress and maximum shear stress [17].…”
Section: Iosipescu Test On Specimens Without Groovesmentioning
confidence: 84%
“…Since shear strength for some polymers are lower than their tensile strength [3,17], shear type cracking can occur at the yielding and crack initiation stage [2] in cases that the ratio of the applied shear stress to tensile stress is high. However, the subsequent fracture mode may switch to mode I as the crack and the accompanied plastic deformation zone evolve.…”
Section: Review Of Fracture Analysis Using Classical Lefmmentioning
confidence: 99%
See 2 more Smart Citations
“…In an Finite Element Method (FEM) analysis, Aoki et al (1987) concluded that shear fracture in an aluminum alloy becomes more pronounced as the mode II component increases. Studies of fracture behavior of polymer alloys under various mixed mode loadings showed that crack initiation occurs in the opening-type fracture followed by the transition fracture from the opening-type to the shear-type fracture (Husaini et al, 2001;Husaini et al, 2000;Husaini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%